Sistem Informasi Absensi Karyawan Outsourcing PT. Cipta Karya Madya - Yusuf Sutanto - Universitas Dharma AUB Surakarta (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - Presence or also known as attendance is an activity of collecting data to determine the number of attendance at an event. Any activity that requires information about participants will certainly make attendance. Any activity that requires information about participants will certainly make attendance. Such as documents that record the hours of attendance of each employee in the company. The record of the employee's attendance can be in the form of an ordinary attendance list, or it can also be in the form of an attendance card filled with a time recording machine. The work schedule determined through employee attendance is often of particular concern in salary distribution because it is closely related to an employee's productivity and contribution while doing work in a company. This research aims to produce an information system for employee attendance which already includes management of work shifts, work leave, overtime hours and permission not to work. With this integrated system, it will be easier to calculate salaries. The Software Development method used is the waterfall method. Keywords - Presence, outsourching employee, web base, waterfall Abstrak - Presensi atau biasa disebut juga absensi adalah sebuah kegiatan pengambilan data guna mengetahui jumlah kehadiran pada suatu acara. Setiap kegiatan yang membutuhkan informasi mengenai peserta tentu akan melakukan absensi. Seperti dokumen yang mencatat jam hadir setiap karyawan di perusahaan. Catatan jam hadir karyawan tersebut dapat berupa daftar hadir biasa, dapat juga pula berbentuk kartu hadir yang diisi dengan mesin pencatat waktu. Jadwal kerja yang ditentukan melalui absensi kehadiran karyawan seringkali menjadi perhatian khusus dalam pemberian gaji karena sangat berhubungan erat dengan produktivitas seorang karyawan dan kontribusi selama melakukan pekerjaan di suatu perusahaan. Penelitian ini bertujuan untuk menghasilkan sistem informasi kehadiran karyawan yang di dalamnya sudah terdapat pengelolaan shift kerja, cuti kerja, jam lembur dan ijin tidak masuk kerja. Dengan adanya sistem yang sudah terintegrasi tersebut akan dapat memudahkan dalam perhitungan gaji. Metode Pengembangan Perangkat Lunak yang digunakan adalah metode waterfall. Kata Kunci: absensi, karyawan outsourcing, berbasis web, waterfall